Medical practice as the basis of philosophical culture dr. E. V. Multich - A. Y. Ionov; T. A. Kovelina (Кубанский научный медицинский вестник, 2016)
The article reveals one of the pages of the history of regional medicine in the life and work of the famous Kuban medical researcher Eugene V. Multich (1917-2002). Due to the influence of the medical profession on the formation of values and beliefs about the world, about the philosophical and moral side of his personality.